Analysis of the effect 3D printing parameters on tensile strength using Copper-PLA filament - Mahros Darsin; Renald Rochman Mauludy; Intan Hardiatama; Boy Arief Fachri; Mochamad Edoward Ramadhan; Doddy Parningotan (SINERGI, 2022)
This research aims to find the optimal combination of parameters to obtain the maximum tensile strength of 3D printing products made of eCopper, which consists of 45% Cu and 55% PLA. The parameters used were nozzle temperature, layer height, print speed and bed temperature with three levels each. The Taguchi L9 (3^4) experiment was used for design and analysis. The product was printed in the form of a tensile test specimen according to the ASTM D638 Type I standard using a Cartesian FDM 3D printer. The average response S/N ratio calculation found that the highest tensile strength would be obtained when applying combination parameters of nozzle temperature 230 oC, layer height 0.35 mm, print speed 90 mm/s and bed temperature 60 oC. While each parameter contributes to the tensile strength by the order are nozzle temperature, layer height, print speed, and bed temperature 59.44%, 20.53%, 18.06% and 1.97%, respectively.